AUDIT FINDINGS COMMUNICATION BARRIERS IN PUBLIC SECTOR - Ahmad Fachrudin; Adib Faishol (Universitas Mercu Buana, 2026)
his study examines communication barriers in conveying and following up on public sector audit findings by positioning the psychological and sociological dimensions of bureaucracy as primary factors influencing audit effectiveness. The study stems from the phenomenon where public sector audit recommendations are frequently not optimally implemented on a substantive level. Existing public audit literature has predominantly focused on technical, compliance, and governance aspects. This study aims to develop a conceptual synthesis demonstrating how communication barriers generate information equivocality within the auditor-auditee relationship and subsequently impact the effectiveness of audit follow-ups. Adopting a qualitative approach, this study employs an integrative literature review method by analyzing reputable Scopus-indexed scientific articles, academic books, and relevant supporting literature encompassing organizational communication, public sector audit, resistance to change, power distance, defensive silence, and information equivocality. A thematic analysis was performed through concept classification, variable relationship synthesis, and theoretical integration to elucidate the underlying mechanisms through which audit communication barriers form within public sector organizational environments. The findings reveal that audit communication barriers represent a multidimensional phenomenon shaped by the interplay between organizational psychological and sociological factors. On the psychological dimension, audit anxiety, organizational pressures, defensive silence, and defensive routines such as cover-ups and pretense prompt auditees to restrict information disclosure, resist findings, and hinder the follow-up of audit recommendations. On the sociological dimension, a hierarchical culture characterized by high power distance and the practice of